Effects of grazing on the performance and behaviour of beef bulls - Huuskonen, Arto; Tuomisto, Leena; Jansson, Susanna; Martiskainen, Paula; Ahola, Leena; Kauppinen, Risto (ee, 2007)
We compared performance and behaviour of finishing Hereford bulls raised at pasture and in an uninsulated barn. Grazing led to leaner carcasses and improved the content of healthy fatty acids (e.g. CLA) in the meat, making the meat more compatible with consumer requirements. Differences in the time-budgets between the housing environments resulted mostly from the different feeding regimes and different space allowances. Stereotyped tongue-rolling was absent and there were no differences between the environments in time spent butting. This indicates that both housing environments were satisfactory in regard to the bulls' welfare. However, more synchronised behaviour in the pasture bulls indicates better opportunities for species-typical social behaviour at pasture.
Keywords: Ko; laiduntaminen; naudanlihantuotanto; sonnit; kasvu; rasvahapot; käyttäytyminen; grazing; beef production; bulls; growth; fatty acids; behaviour